Determinants of Focused Antenatal Care Uptake among Women in Tharaka Nithi County, Kenya - Eliphas Gitonga (Advances in Public Health)
Background. The health status of women is an important indicator of the overall economic health and well-being of a country. Maternal health is closely linked with the survival of newborns. For every woman who dies, about thirty others suffer lifelong injuries. Focused antenatal care is one of the interventions to reduce maternal morbidity and mortality. It recommends four targeted visits during pregnancy within which essential services are offered. The aim of the study was to assess the determinants of uptake of focused antenatal care among women in Tharaka Nithi County, Kenya. Methods. This was a descriptive cross-sectional survey. Stratified sampling was used to select the health facilities while systematic sampling was used to select the respondents. Chi square, Fisher’s exact test, and logistic regression were used to analyse the data. Results. The level of uptake of focused antenatal care was slightly more than half (52%). The determinants of uptake of focused antenatal care are level of education, type of employment, household income, parity, and marital status of the pregnant women. Conclusion. Despite high attendance of at least one antenatal visit in Kenya, the uptake of focused antenatal care is proportionally low.